Modelling the Crop Water Requirement in Batticaloa District, Sri Lanka: FAO-Cropwat Modelling for Rice - Narmilan, A.; Sugirtharan, M. (University of Jaffna, 2018)
Agriculture still the leading source of livelihood and contributes a great percentage to national income for most developing countries around the world. Since agriculture is the major user of water, improving agricultural water management is essential to any irrigation management approach specially to apply the exact amount of water to the field in order to meet crop water requirement. This study aims to estimate water requirement of rice by using the model CROPWAT. In this study, water requirement of rice for the two seasons were studied. The results show that, Batticaloa district receives around 1060mm effective rainfall per year. ETO value ranged between 3.07 and 4.57mm/day during December to April respectively. ETC value recorded as 1.76 to 3.66 mm/day during November to January respectively. In Maha season, crop water requirement of rice increases at the rate of 1.85 mm/day at initial stage to 3.3 mm/ day in the mid stage of growth. The water requirement of rice decreases from 3.46 mm/day in the late- season to 3.03mm per day during the period of harvesting. In Yala season, ETC values were recorded as in between 2.13 to 4.5 mm/day during the period of May to July. The water requirement of rice decreases from 4.5 mm/ day to 3.29 mm per day during the late season to the period of harvesting. According to the study, effective rainfall were found to be 601.4 and 298.5 mm/ decade in Maha and Yala season respectively, and total crop water requirement are 349.2 and 436.7 mm/ decade in Maha and Yala season respectively. Therefore the model for planning of irrigation water requirements of rice is very important for efficient utilization of water and to meet the possible change of climate in agricultural sector
Keywords: Cropwat; effective rainfall; evapotrans piration; rice water requirement